Pessoas, Qualidade e Gestão do Conhecimento - Brito, Elisabeth (2011)
The literature on quality management and knowledge management underlines the importance of an appropriate way of managing people so that their implementation occurs with the required success. Our perspective considers people as the fundamental piece in optimizing the organizational results arising from adoption of these two management philosophies. It is in this context that the article reflects on the importance of people and the role attributed to/demanded of them in quality management and knowledge management, considering also the relationships between these two management philosophies. In the reflection carried out, we took into consideration different theoretical contributions from the literature on the subject, which we will attempt to systematize and articulate.